2020
DOI: 10.1371/journal.ppat.1008418
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium simiae: Harmless colonizer or deadly pathogen?

Abstract: What is the history of Mycobacterium simiae and what are some of its genomic components?

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…M. simiae infections were most common in females and older patients than other NTM isolates in the current study. In general, men are more likely than Jabbour et al 2020). We found that the M. simiae positive cases in our study had obesity, HIV, cystic fibrosis, diabetes mellitus, and asthma as underlying diseases.…”
Section: Discussionmentioning
confidence: 49%
“…M. simiae infections were most common in females and older patients than other NTM isolates in the current study. In general, men are more likely than Jabbour et al 2020). We found that the M. simiae positive cases in our study had obesity, HIV, cystic fibrosis, diabetes mellitus, and asthma as underlying diseases.…”
Section: Discussionmentioning
confidence: 49%
“…For M. simiae infections, a combination of three drugs including a macrolide seems to be favourable. 19 20 Based on the in vitro investigations of van Ingen et al , moxifloxacin, a macrolide and a third antibiotic class (eg, clofazimine and streptomycin, an aminoglycoside such as amikacin) should be included in treatment regimens for a M. simiae infection. 21 22 Azithromycin and clarithromycin are assumed to be equally effective.…”
Section: Discussionmentioning
confidence: 99%
“…M. simiae is a member of the Mycobacterium simiae complex, which compromises some 19 species. Infection with M. simiae was first reported in rhesus monkeys and has since been isolated in many countries, notably Cuba and the Middle East, with growing incidences in Europe and South East Asia [ 5 ]. It may be acquired from water [ 6 ] as well as nosocomial sources [ 7 ], and antibiotic resistance, as was present in this case, is common.…”
Section: Discussionmentioning
confidence: 99%